A Novel Agent Enhances the Chemotherapeutic Efficacy of Doxorubicin in MCF-7 Breast Cancer Cells - Wang, Liang; Chan, Judy Y.; Zhou, Xinhua; Cui, Guozhen; Yan, Zhixiang; Wang, Li; Yan, Ru; Di, Lijun; Wang, Yuqiang; Hoi, Maggie P.; Shan, Luchen; Lee, Simon M. (Frontiers in Pharmacology, 2016)
We have previously demonstrated that DT-010, a novel conjugate of danshensu (DSS) and tetramethylpyrazine (TMP), displays antitumor effects in breast cancer cells both in vitro and in vivo. In the present study, we investigated whether DT-010 enhances the chemotherapeutic effect of doxorubicin (Dox) in MCF-7 breast cancer cells and exerts concurrent cardioprotective benefit at the same time. Our findings showed that DT-010 was more potent than TMP, DSS or their combination in potentiating Dox-induced toxicity in MCF-7 cells. Co-treatment with DT-010 and Dox increased apoptosis in MCF-7 cells relative to Dox alone. Further study indicated that glycolytic capacity, glycolytic reserve and lactate level of MCF-7 cells were significantly inhibited after DT-010 treatment. DT-010 also increased the expression of the pro-survival protein GRP78, which was inhibited by co-treatment with Dox. Both endoplasmic reticulum (ER) stress inhibitor 4-PBA and knockdown of the expression of GRP78 protein potentiated DT-010-mediated apoptosis in MCF-7 cells. Moreover, DT-010 inhibited Dox-induced cardiotoxicity in H9c2 myoblasts. In conclusion, DT-010 and Dox confers synergistic anti-tumor effect in MCF-7 breast cancer cells through downregulation of the glycolytic pathway and inhibition of the expression of GRP78. Meanwhile, DT-010 also protects against Dox-induced cardiotoxicity.